Effect of Soaking Treatment to Oil Palm Empty Fruit Bunches Wettability and Its Comparison with Several Woods Wettablility - Tito Sucipto; Surdiding Ruhendi (FORESTA, 2012)
The wettability in term of corrected water absorption height (CWAH) of treated oil palm empty fruit bunches (TKS) particles and compare with some woods wettablility was investigated. The treatments were soaking TKS in cold water, hot water and ethanol–benzene. The objective of the research was to know the effect of soaking treatment on the wettability as indicator of gluability of the TKS particles adhesion strength and its comparison with several woods wettablility. The research results show that the CWAH of the TKS which were soaked in cold water, hot water and ethanol–benzene were 72 mm, 202 mm and 214 mm, respectively. Meanwhile the CWAH of untreated TKS was only 46 mm, were lower than those the treated ones. The analysis of variance shows that the soaking treatment in ethanol–benzene and hot water significantly and positively affect wettability. Generally, CWAH of the TKS was lower than other woods, which effected by density, porousity and extractive difference.Keywords: oil palm empty fruit bunches, soaking treatment, wettability